Extracellular self-RNA: A danger elicitor in pepper induces immunity against bacterial and viral pathogens in the field - Kim, Doyeon; Riu, Myoungjoo; Oh, Sang-Keun; Ryu, Choong-Min (Frontiers in Plant Science, 2022)
Plants and animals serve as hosts for microbes. To protect themselves from microbe-induced damage, plants and animals need to differentiate self-molecules/signals from non-self, microbe-derived molecules. Damage-associated molecular patterns (DAMPs) are danger signals released from the damaged host tissue or present on the surface of stressed cells. Although a self-extracellular DNA has previously been shown to act as a DAMP in different plant species, the existence of a self-extracellular RNA (eRNA) as a danger signal in plants remains unknown. Here, we firstly evaluated the ability of a pepper self-eRNA to activate immunity against viral and bacterial pathogens under field conditions. Pepper leaves pre-infiltrated with self-eRNA exhibited reduced titer of the naturally occurring Tomato spotted wilt virus and diminished symptoms of Xanthomonas axonopodis pv. vesicatoria infection through eliciting defense priming of abscisic acid signaling. At the end of the growing season at 90 days after transplanting, pepper plants treated with self- and non-self-eRNAs showed no difference in fruit yield. Taken together, our discovery demonstrate that self-eRNA can successfully activate plant systemic immunity without any growth penalty, indicating its potential as a novel disease management biological control agent against a broad range of pathogenic microbes.